The importance of reliability in the Multidimensional Poverty Index for Latin America (MPI-LA) - Santos, M; Villatoro, P (Routledge, 2019)
We recently proposed a Multidimensional Poverty Index for the Latin America (MPI-LA) region implementing a broadly used methodology developed by Sabina Alkire and James Foster. The present note is a response to Hector Najera and David Gordon’s paper (published in this volume), in which they claim that the MPI-AL is an ‘unreliable measure of poverty’ because it does not pass some statistical tests that they consider applicable to multidimensional poverty measurement. In this note we address each of their critiques in turn and explain why Najera and Gordon’s claim is not correct.